2009
DOI: 10.1167/iovs.08-3148
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Bevacizumab after Topical, Subconjunctival, and Intravitreal Administration in Rabbits

Abstract: Intravitreal injection of bevacizumab was the most effective route of administration for intraocular tissue. Also, bevacizumab injected subconjunctivally was transported into the intraocular tissues of the treated eyes at an effective level. Both intravitreal and subconjunctival injections of bevacizumab resulted in high plasma concentrations. Bevacizumab was distributed into the intraocular tissues in fellow eyes via the systemic circulation. This treatment may be effective for blocking vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
190
3
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(218 citation statements)
references
References 52 publications
17
190
3
8
Order By: Relevance
“…However, a longer half-life in ocular tissues after subconjunctival injection bevacizumab compared with intravitreal injection or even topical application via eye drops suggests that bevacizumab accumulates in the scleral matrix. 12 Attempting to control excessive scarring during the shortto-medium term after surgery is associated with higher success rates, and instances in which failing surgeries were rescued by using subsequent procedures have been described over the last 20 years. 21,22 After considering some pharmacokinetic issues and the necessity of the prolonged release of antiscarring drugs during the trabeculectomy postoperative period, we proposed the use of subconjunctival implants as a new bevacizumab delivery system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a longer half-life in ocular tissues after subconjunctival injection bevacizumab compared with intravitreal injection or even topical application via eye drops suggests that bevacizumab accumulates in the scleral matrix. 12 Attempting to control excessive scarring during the shortto-medium term after surgery is associated with higher success rates, and instances in which failing surgeries were rescued by using subsequent procedures have been described over the last 20 years. 21,22 After considering some pharmacokinetic issues and the necessity of the prolonged release of antiscarring drugs during the trabeculectomy postoperative period, we proposed the use of subconjunctival implants as a new bevacizumab delivery system.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is subconjunctival delivery, but it is expected to have a short duration of action and would therefore require repetitive injections. 12 Polyurethane implants (PUIs) have been investigated extensively for use in biomedical applications as scaffolds for tissue regeneration and as controlled-/sustained-release drug delivery systems because of their excellent biocompatibility, chemical versatility, and mechanical properties. [13][14][15] No previous study has evaluated the use of anti-VEGF antibodies associated with PUIs in the eye, so the aim of the present study was to demonstrate the release of active bevacizumab from PUIs in an experimental model of glaucomafiltering surgery in rabbits.…”
Section: Introductionmentioning
confidence: 99%
“…systemic circulation. For example, Nomoto et al have reported that plasma concentrations of bevacizumab increase immediately after subconjunctival administration in rabbits 17 . In the present study, antibody concentrations in the plasma had increased by 3 h after injection data not shown , and concentrations in the contralateral retina increased similar to those in the injected eye Table 1 .…”
Section: Discussionmentioning
confidence: 99%
“…It is easy and noninvasive. Intravitreal and subconjunctival injections achieved a high concentration in plasma and also in the fellow eye through systemic circulation after being absorbed systemically [42].…”
Section: Discussionmentioning
confidence: 99%